Investigating White-Collar Crime Evaluation of Fraud Examinations - Gottschalk, Petter (Springer International Publishing, 2018)
This book examines internal fraud investigations in public and private organizations. It provides a theoretical framework of white-collar crime and convenience theory, to examine a number of case studies, including some cases brought to light by the Panama Papers. Investigating white-collar crime is distinguished from other types of crime by: concealment of the crime rather than the criminal, victims who may be unaware of the crime and not directly visible to the criminal, and the resources available to suspects. It requires a unique strategy and a unique set of tools. This work provides insight into a number of internal investigation reports that are normally not publicly available. It will be of interest to researchers in criminology and criminal justice, particularly with an interest in white collar crime and corruption, as well as related fields such as business, management, economics, and public administration.